Abalone‐Inspired Adhesive and Photo‐Responsive Microparticle Delivery Systems for Periodontal Drug Therapy. Issue 30 (30th August 2022) - Song, Chuanhui; Huang, Danqing; Zhao, Cheng; Zhao, Yuanjin
Abstract: Antibiotics provide promising strategies for treating periodontitis, while their delivery and controllable release with desired oral retention remain challenging. Here, inspired by the unique suction‐cup structures of abalones, a novel adhesive and photo‐responsive microparticle (MP) delivery system is developed to treat periodontitis through microfluidic electrospray technology. Such MPs are generated by quickly ionic cross‐linking of sodium alginate together with photo‐curing of poly(ethylene glycol) diacrylate of the distorted microfluidic droplets during their high‐speed dropping into calcium chloride solution. Attributing to their unique concave structures, the abalone‐inspired MPs exhibit desired underwater adhesion ability and stability under running water. In addition, due to the loading of antibiotics minocycline hydrochloride and near‐infrared (NIR)‐responsive black phosphorus during their fabrication, the resultant MPs can not only eradicate bacteria directly, but also realize a controllable and effective drug release upon NIR irradiation. Based on these features, it is demonstrated from in vivo periodontitis that the abalone‐inspired MPs are firmly adhesive and can controlled‐release drugs on the tooth, and thus have outstanding antibacterial efficacy against Porphyromonas gingivalis . These results indicate the particular values of the abalone‐inspired MPs for oral‐related disease treatment. Abstract : By encapsulating the black phosphorus and minocycline hydrochloride, the abalone‐inspired microparticles with the enhanced adhesive ability and controllable drug release capacity can realize antibacterial photothermal therapy on the tooth.